Studi Komposisi Sampah Non Domestik Di Wilayah Pengembangan II Dan III Kota Pekanbaru - Vera Fitriani; Elvi Yenie; Gunadi Priyambada (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Garbage can be a problem that cannot be ignored because year after year the amount of waste generated has increased. This study aims to determine the composition of waste in the Development Areas II and III Pekanbaru City. This research was conducted based on SNI 19-3964-1994 method for eight consecutive days. The composition of waste in the Development Area II of Pekanbaru City is 47,08% food waste, 9,99% leaves waste, 17,58% paper waste, 13,8% plastic paper, sanitary waste 3,63%, garbage styrofoam by 0,73%, wood waste by 1,8%, canned waste by 1,3%, glass waste by 0,5% and fabric waste by 0,26% and the composition of waste in Development Region III are food waste by 52, 32%, leaves waste by 11,01%, paper waste by 17,15%, plastic waste by 14,01%, sanitary waste by 2,94%, styrofoam waste by 1.62%, wood waste by 0,53% , garbage cans of 0,07%, glass waste of 0,37% and fabric waste of 0,05%. Waste composition in Development Areas II and III Pekanbaru City is dominated by wet waste. The largest composition of waste in Development Region II is food waste by 47,08% and in Development Region III is food waste by 52,32%.Keywords: Composition of waste, Development Areas II and III Pekanabru City